The antecedents of brand equity development on Malaysian interment service providers - Nikhashemi, Seyed Rajab; Paim, Laily; Md Sidin, Samsinar; Osman, Syuhaily (IDOSI Publications, 2013)
This study attempts to identify the critical antecedents in the formation of solid brand equity in Malaysian Internet service provides which called, TMnet, Jaring, P1 Wimax and Maxis. However the paper proposes tests and investigates theoretical framework of the antecedents of brand equity by employing structure equation modeling (SEM) and collecting survey data from the large sample of Malaysian internet subscribers. Result confirmed that, all four of brand equity antecedents have stronger causal relationships with brand equity, Moreover results supported that perceived quality and consumer loyalty are the most determining factors for developing brand equity in Malaysian internet service providers. This research restricted to the selection of four brands. Clearly, a variety of choice situation must be investigated before generalizable comments can be made to guide the development of brand equity. Another limitation of the present study is the size and composition of the group which participated in the study. The outcomes provide insights to Malaysian internet service providers and other organizations of similar structure regarding how they may possibly manage marketing strategies for enhanced business performance.